Análise da temperatura ótima de corte para o par: metal duro revestido vs. aço ABNT 1045 - Verner Petersen Pereira (2019)
The optimization of cutting parameters in metal machining has been a considerable concern in the manufacture of parts from various industries. Reducing the wear of the tool and improving the quality of the machined surface are some of the goals in the optimization of the cutting process. In this sense, the cutting temperature has been shown to be the most adequate parameter to correlate tool wear, surface integrity and also cutting force. Thus, the overall objective of this research was to validate the existence of an optimum cutting temperature where the minimum wear rate, minimum cutting force and higher quality machined surface could be achieved. For this, the methods of lower stabilized cutting force and better machined surface quality were used in the dry turning of ABNT 1045 steel annealed using coated cemented carbide inserts PVD - (Al, Ti)N varying the cutting parameters feed rate and cutting speed. The cutting temperature was obtained by infrared radiation. In a second moment, to check if the lesser wear coincides with the lower cutting force and better roughness of the machined surface, tool wear tests were performed measuring flank wear, notch wear and mass loss of the inserts at different cutting speeds. The results showed that it was not possible to validate the existence of an optimum cutting temperature by the proposed methods, since different temperatures corresponding to the beginning of the stabilization of the cutting forces (402 a 460) ºC were found and these temperatures were rising with increasing feed rate. The roughness values had small and random variations in the same feed rate with increasing temperature and cutting speed. The cutting forces in the same feed rate presented the highest values at the lower cutting speeds and from a certain speed they were stabilized, however the cutting temperatures increased continuously with the cutting speed. The results of the three tests of tool wear pointed to an increasing wear with the increase of the cutting speed, with that, found that the less wear did not occur in the minimum cutting force.